National ideology in Malaysian children’s novels: An analysis of the novel Anak Din Biola - Misran Rokimin (Journal of Faculty of Social Sciences and Humanities. Universiti Kebangsaan Malaysia, 2006)
This article aims to examine the connection between the government’s national ideology, Rukunegara, and the novel Anak Din Biola (The Fiddler’s Son). This novel is selected as the focus of discussion in this article as it has been chosen to be the official text for the Bahasa Melayu subject (KOMSAS) for Form One. Analysis of the novel will be based on two elements, that is, character and plot of the novel, with special attention on the main character of the novel. Content analysis of the novel will be carried out using two principles of the Rukunegara, that is, “Rule of Law” and “Good Behaviour and Morality” as tools of reference. The results of the content analysis illustrate the ways in which the author projects the Rukunegara values through the characters and plot of his novel